2018
DOI: 10.1002/jcb.27507
|View full text |Cite
|
Sign up to set email alerts
|

Blocking CXCR1/2 contributes to amelioration of lipopolysaccharide‐induced sepsis by downregulating substance P

Abstract: The results of this study indicate that blockade of CXCR1/2 may represent a promising therapeutic strategy for the treatment of sepsis-associated ALI through regulation of neuropeptides and necroptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
(52 reference statements)
2
5
0
Order By: Relevance
“…Largely in agreement with our findings, miR‐326 activates the NF‐κB signalling pathway through target inhibition of B cell leukaemia/lymphoma 2–related protein A1, by which inflammatory responses and lung injuries of mice with ALI were aggravated 41 . More importantly, function studies have shown that the inactivation of the NF‐κB signalling pathway can reduce oxidative stress to allow improvement of ALI; CXCR1/2 antagonists can ameliorate LPS‐induced ALI in association with sepsis 42,43 . Concordantly, the addition of PDTC, an inhibitor of the NF‐κB signalling pathway, resulted in alleviated lung injuries induced by NET, as observed in mouse models of TRALI in our study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Largely in agreement with our findings, miR‐326 activates the NF‐κB signalling pathway through target inhibition of B cell leukaemia/lymphoma 2–related protein A1, by which inflammatory responses and lung injuries of mice with ALI were aggravated 41 . More importantly, function studies have shown that the inactivation of the NF‐κB signalling pathway can reduce oxidative stress to allow improvement of ALI; CXCR1/2 antagonists can ameliorate LPS‐induced ALI in association with sepsis 42,43 . Concordantly, the addition of PDTC, an inhibitor of the NF‐κB signalling pathway, resulted in alleviated lung injuries induced by NET, as observed in mouse models of TRALI in our study.…”
Section: Discussionsupporting
confidence: 89%
“…41 More importantly, function studies have shown that the inactivation of the NF-κB signalling pathway can reduce oxidative stress to allow improvement of ALI; CXCR1/2 antagonists can ameliorate LPS-induced ALI in association with sepsis. 42,43 Concordantly, the addition of PDTC, an inhibitor of the NF-κB signalling pathway, resulted in alleviated lung injuries induced by NET, as observed in mouse models of TRALI in our study.…”
Section: Discussionsupporting
confidence: 78%
“…In this context, antagonists of IL-8 are already used in the treatment of severe inflammatory conditions. However, the data are still limited and partly inconsistent [38-40]. Overall, IL-8 clearly plays an important role during systemic inflammation [6, 9, 10, 41, 42].…”
Section: Introductionmentioning
confidence: 99%
“…References NF-κB pathway and macrophages release pro-inflammatory cytokines, leading to lung inflammation and injury The expression of CXCR1/2 and p-MLKL is high, and the SP level is high while the VIP level is low. All could be reversed by reparixin, a CXCR antagonist that increased the survival rate mice of mice and improved lung inflammation Wang et al (2018b) hyperoxic acute lung injury (HALI)…”
Section: More Specific Main Content About Necroptosismentioning
confidence: 99%